Identification of reversible changes in cerebral fat embolism syndrome using susceptibility‐weighted imaging: A case report. Issue 4 (14th April 2020) - Hidaka, Masaoki; Murao, Kei; Yokoi, Mio; Kuwano, Miyuki; Mezuki, Satomi; Osaki, Masato; Akiyama, Tomoaki; Yamaguchi, Shinya; Sayama, Tetsuro; Kitazono, Takanari; Arakawa, Shuji
Abstract: A 90‐year‐old female with traumatic femur fracture developed dyspnea and consciousness disturbance. Susceptibility‐weighted imaging of the brain revealed multiple punctate low‐signal‐intensity lesions throughout the cerebral white matter, and cerebral fat embolism was diagnosed. The symptoms recovered with conservative treatment, while magnetic resonance imaging scans showed the amount of susceptibility‐weighted imaging lesions markedly increased on day 7 and moderately decreased on day 20. Although susceptibility‐weighted imaging lesions in cerebral fat embolism are thought to be petechiae and last through the whole course without significant change, the reversal of the susceptibility‐weighted imaging findings in our case might reflect a susceptibility change due to chronological hemoglobin degeneration and reperfusion of cerebral microcirculation.